Characterisation of Mass Transfer in Frontal Nanofiltration Equipment and Development of a Simple Correlation - Oatley-Radcliffe, Darren L.; Williams, Steffan R.; Lee, Christopher; Williams, Paul M. (Journal of Membrane and Separation Technology, 2016)
This aim of this work was to investigate the effects of mass transfer in three commercially available frontal nanofiltration systems (Amicon, Sterlitech and Membranology) using the rejection of uncharged poly ethylene glycol (molecular weight 3400) at different pressures and stirrer speeds using a 4000 MWCO membrane. The real rejection was calculated from the observed rejection using the infinite rejection method and a comparison was made between experimentally obtained mass transfer coefficients and those obtained from commonly used ultrafiltration theory. A new mass transfer correlation was proposed that is more appropriate to account for the increased mass transfer effects observed with the larger pressures of nanofiltration. This new correlation is defined as NSh = j(NRe)n (NSc)0.33(1+(Jv/wr)x) is only a minor modification to existing theory and has an accuracy suitable for engineering design purposes.